Exocrine Pancreatic Insufficiency in Diabetic Patients: Prevalence, Mechanisms, and Treatment - Matteo Piciucchi; Gabriele Capurso; Livia Archibugi; Martina Maria Delle Fave; Marina Capasso; Gianfranco Delle Fave (International Journal of Endocrinology)
Pancreas is a doubled-entity organ, with both an exocrine and an endocrine component, reciprocally interacting in a composed system whose function is relevant for digestion, absorption, and homeostasis of nutrients. Thus, it is not surprising that disorders of the exocrine pancreas also affect the endocrine system and vice versa. It is well-known that patients with chronic pancreatitis develop a peculiar form of diabetes (type III), caused by destruction and fibrotic injury of islet cells. However, less is known on the influence of diabetes on pancreatic exocrine function. Pancreatic exocrine insufficiency (PEI) has been reported to be common in diabetics, with a prevalence widely ranging, in different studies, in both type I (25–74%) and type II (28–54%) diabetes. A long disease duration, high insulin requirement, and poor glycemic control seem to be risk factors for PEI occurrence. The impact of pancreatic exocrine replacement therapy on glycemic, insulin, and incretins profiles has not been fully elucidated. The present paper is aimed at reviewing published studies investigating the prevalence of PEI in diabetic patients and factors associated with its occurrence.